Implementation of cancer guidelines in Pakistan: A call for action - Memon, Areeba; Memon, Minahil; Memon, Dua Mahfooz (Journal of the Pakistan Medical Association, 2025)
Cancer remains a pervasive threat to global health, ranking among the leading causes of mortality worldwide. In 2020 alone, an estimated 19.3 million new cases of cancer emerged, leading to approximately 10 million deaths. A staggering rise in cancer cases is expected to reach 28.4 million by 2040.1 According to the World Health Organization (WHO), Pakistan, a low-resource country grappling with its own burden of cancer, witnessed 0.17 million new cases and 0.12 million cancer deaths in 2018.2 Despite the availability of clear and well-framed age-based screening guidelines such as those provided by the United States Preventive Services Task Force (USPSTF), their utilisation remains notably deficient in Pakistan. This deficiency can be attributed to a myriad of factors including inadequate healthcare policies and infrastructure for the implementation of screening protocols, lack of accountability on the part of the healthcare institutions and the government, as well as nationwide economic challenges. Insufficient patient counselling and limited awareness of guidelines among patients and physicians compound the challenges in adhering to USPSTF screening guidelines. Given Pakistan’s high disease burden, it is imperative to prioritise education among healthcare workers on the importance of secondary prevention through structured screening protocols. Implementation of such protocols can be incorporated into the physician performance assessment and hospital quality metrics on a broader scale. A robust and effective national cancer prevention and control programme must be established, which maintains an updated health registry that documents cancer prevalence, devises strategies to address cases and holds healthcare professionals and organisations accountable for any negligence. In addition, educational initiatives (via electronic and social media) to create mass awareness regarding the age-appropriate screening recommendations to reach an audience at a greater scale.3 As we confront this escalating crisis, it becomes important for us to establish a sustainable groundwork to propagate preventive measures and adequate cancer care. Addressing these challenges is pivotal for achieving effective global cancer control and safeguarding public health. Further, research focusing on barriers specific to low-income countries like Pakistan is warranted for targeted interventions to improve outcomes in cancer prevention and control in a proactive and cost-effective manner.